Traumatic Brain Injury: A Forensic Approach: A Literature Review - Bertozzi, Giuseppe; Maglietta, Francesca; Sessa, Francesco; Scoto, Edmondo; Cipolloni, Luigi; Di Mizio, Giulio; Salerno, Monica; Pomara, Cristoforo (Current Neuropharmacology, 2020)
Traumatic brain injury (TBI) is the principal cause of invalidity and death in the population under 45 years of age worldwide. This mini-review aims to systematize the forensic approach in neuropathological studies, highlighting the proper elements to be noted during external, radiological, autoptical, and histological examinations with particular attention paid to immunohistochemistry and molecular biology. In the light of the results of this mini-review, an accurate forensic approach can be considered mandatory in the examination of suspected TBI with medico-legal importance, in order to gather all the possible evidence to corroborate the diagnosis of a lesion that may have caused, or contributed to, death. From this point of view, only the use of an evidence-based protocol can reach a suitable diagnosis, especially in those cases in which there are other neuropathological conditions (ischemia, neurodegeneration, neuro-inflammation, dementia) that may have played a role in death. This is even more relevant when corpses, in an advanced state of decomposition, are studied, where the radiological, macroscopic and histological analyses fail to give meaningful answers. In these cases, immune-histochemical and molecular biology diagnostics are of fundamental importance and a forensic neuropathologist has to know them. Particularly, MiRNAs are promising biomarkers for TBI both for brain damage identification and for medico-legal aspects, even if further investigations are required to validate the first experimental studies. In the same way, the genetic substrate should be examined during any forensic examination, considering its importance in the outcome of TBI.
Keywords: forensic radiology